The Effects Of 2D And 3D Representations In Second Life On Students’ Perception And Performance In Learning Java Programming In Saudi Arabia - Bassfar, Zaid Aslm (2014)
The researcher found that most computer science’s students have a limited understanding of the main concepts of Java and have difficulties in visualizing learning spaces. The researcher aims to study the ability of students to understand the concepts of learning Java when writing codes. This study examined the attitudes, perceptions, motivations, self-efficacies, and achievements of the students in the Teachers’ College, Saudi Arabia by comparing the contributions of a three dimensional (3D) representation to such factors with the contributions of a two dimensional (2D) representation. Pengkaji mendapati bahawa kebanyakan pelajar sains komputer mempunyai pemahaman konsep Java yang terhad dan disebabkan ini, mereka seringkali mengalami kesulitan dalam visualisasi ruang pembelajaran. Justeru itu, pengkaji berharap untuk meningkatkan kebolehan para pelajar agar memahami ketelitian konsep mempelajari Java secara lebih jelas dalam penulisan kod. Kajian ini meneliti aspek sikap, persepsi, motivasi, keupayaan diri dan pencapaian pelajar di Kolej Perguruan, Arab Saudi dan perbandingan dalam penggunaan dua dimensi (2D) dan tiga dimensi (3D) serta faktor-faktor yang terlibat telah dilakukan.